Relationships between Judaism and politics through the making of memory among progressive Jews - Setton, Damián (Facultad de Filosofía y Humanidades. Museo de Antropología, 2023)
As a contribution to both Jewish studies and studies on Kirchnerism, the paper analyses how political categorization takes place inside the Jewish field. During the last stretch of Cristina Fernandez Presidency, Judaism becomes one of the main dimensions of the discourses and strategies of some political actors whose objective was the making of an antikirchnerist stance. It was in this very context, and as a reply to those strategies, that the Llamamiento Argentino Judío was founded. The LAJ was created as an organization aimed at supporting the government and to contest the claiming of DAIA of being recognized as the only representative of Argentinean Jews. The LAJ projected a kind of definition of Jewishness which dived into the Left- Right scheme of political categorization. This way, the LAJ articulated both Jewishness and the national-popular movement. The paper analyses how this articulation took place through the memory politics dynamics, taking into account that memory has to be analysed as a not without tensions process.